Place of Residence as a Determinant of Adolescents' Pro-Healthy Lifestyle - Marlena Duda (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The environment in which a person lives is important in shaping their well-being. The place of residence, which is one of the social determinants of health, is at the forefront of health determinants. It therefore seems important to analyse the relationship between the sense of quality of life and lifestyle taking into account social factors in the group of adolescents. Research Aim: In the presented article the relations between the sense of quality of life and healthy lifestyle and significant differences in the range of analysed variables between youth living in urban and rural areas were searched for. Method: The research was conducted by means of a diagnostic survey with the use of the following research tools: KINDSCREEN-52, Cumulated Fatigue Questionnaire (QFIQ), Adolescent Lifestyle Questionnaire (ALQ) and Health Behaviour Inventory (IZZ). Results: The research showed that the place of residence is not important in shaping the sense of quality of life and modelling the type of health behaviours of youth. Conclusions: There is a need for more extensive research into the analysed variables in the context of the participants' social status with some additional variables.